Pelatihan Digital Marketing Melalui Media Sosial pada UMKM Kelompok Binaan Kuliner Dinas Koperasi, UMKM dan Tenaga Kerja Kota Banjarbaru - Novyanti, Rika; Shintia, Novi; Maharani, Sari Heppy; Effendi, Tarman (Politeknik Negeri Banjarmasin, 2020)
The Covid 19 pandemic that occurred throughout the world, more or less brought changes to the function of economic activity in Indonesia. Many business activities have changed, both in terms of business activities and other activities. This is also happen to Middle Group Community Business (UMKM) players in Indonesia in general, as well as in South Kalimantan in particular. Marketing activities that have been carried out in person have begun to shift to online and digital forms, following the Social Restriction policy imposed by the government. This inevitably makes UMKM players have to follow the rhythm of the situation and the appropriate conditions, if they don't want the businesses they manage to be eroded by other businesses that are more adaptive in responding to the conditions and needs of the general public. If all this time UMKM players prefer conventional methods of promotion and marketing, then according to the conditions and needs of the times they must be able to carry out business activities digitally. The implementation of Community Service activities in the form of